2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944065
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum-averaged Harmonic Path (SHAPA) algorithm for non-contact vital sign monitoring with ultra-wideband (UWB) radar

Abstract: We introduce the Spectrum-averaged Harmonic Path (SHAPA) algorithm for estimation of heart rate (HR) and respiration rate (RR) with Impulse Radio Ultrawideband (IR-UWB) radar. Periodic movement of human torso caused by respiration and heart beat induces fundamental frequencies and their harmonics at the respiration and heart rates. IR-UWB enables capture of these spectral components and frequency domain processing enables a low cost implementation. Most existing methods of identifying the fundamental component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
(26 reference statements)
0
17
1
Order By: Relevance
“…Because comparable studies utilizing UWB impulse radar to measure human heart rate through a wall did not quantify the accuracy of their heart rates, it is difficult to compare the results obtained in this paper directly with those of the other studies. However, some studies using UWB impulse radar to extract a heartbeat without wall penetration [ 16 , 17 ] found a minimum error rate of 4.0–5.4%, and even in comparison to these studies, the experimental result of this study demonstrated higher accuracy. The researchers of all comparable studies extracted heart rate in the frequency domain.…”
Section: Experiments and Discussioncontrasting
confidence: 57%
“…Because comparable studies utilizing UWB impulse radar to measure human heart rate through a wall did not quantify the accuracy of their heart rates, it is difficult to compare the results obtained in this paper directly with those of the other studies. However, some studies using UWB impulse radar to extract a heartbeat without wall penetration [ 16 , 17 ] found a minimum error rate of 4.0–5.4%, and even in comparison to these studies, the experimental result of this study demonstrated higher accuracy. The researchers of all comparable studies extracted heart rate in the frequency domain.…”
Section: Experiments and Discussioncontrasting
confidence: 57%
“…They have proposed a method that uses the feature time index with the first valley peak of the energy function of intrinsic mode functions (FVPIEF) calculated by a pseudo bi-dimension ensemble empirical mode decomposition method, which extracts the vital signals by the ensemble empirical mode decomposition (EEMD). In the References [70,71], the authors proposed Harmonic Path and Averaged Harmonic Path algorithms to accurately estimate the vital signs in the presence of breathing harmonics. In another study in Reference [72], a novel noncontract vital sign detection method based on multiple higher order cumulant is presented.…”
Section: Previous Work Related To Vital Signs Extraction From Radar Datamentioning
confidence: 99%
“…In all cases, a direct peak detection of the spectrum of reflected baseband signal is consequently not reliable any more; this requires a spectral estimation algorithm for a robust determination of the frequency components. In [ 22 , 23 ], a harmonic-path algorithm was developed to determine both heartbeat and respiration rates by taking into account all harmonic components of the whole spectrum, but the ambiguity problem is not addressed. A RELAX algorithm was used in [ 24 ] for the spectrum estimation with a 20 GHz Doppler radar, which is based on the minimization of a nonlinear least-square fitting problem.…”
Section: Introductionmentioning
confidence: 99%